Kontekstualisasi Dan Aktualisasi Pendidikan Islam Di Era Kontemporer (Suatu Tinjauan Filsafat Pendidikan Islam) - Maisaroh, Maisaroh; Zuhriyah, Nur Ismi; Sauda, Veralis; Hartono, Djoko (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
This study discusses the process of contextualization and actualization of Islamic education in the contemporary era from the perspective of the philosophy of Islamic education, particularly based on Abdul Wahid’s thought. The era of globalization, digitalization, and secularization of values demands that Islamic education remain relevant without losing its foundational principles. Using a qualitative-descriptive approach through philosophical literature review, this study examines the ontological, epistemological, and axiological aspects of Islamic education. The results show that Islamic education can be contextualized through the reinterpretation of Islamic values to suit modern social and technological dynamics and actualized through the application of moral, spiritual, and social values in educational practice. This process positions Islamic education not merely as knowledge transmission but as a means of forming insān kāmil—a complete human being who is civilized, knowledgeable, and able to balance modernity with spirituality. Thus, Islamic education serves as a transformative force in developing creative, adaptive, and competitive Muslim generations